SPATIAL DISTRIBUTION OF SPECIAL EDUCATION FOR VISION IMPAIRED PEOPLE - Voženílek, Vít; Michalík, Jan; Brychtová, Alžběta; Vondráková, Alena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The article treats spatial analysis distribution of activities within special education of vision impaired children, pupils and students in the Czech Republic. It response to the research questions: What are territorial differences in content and volume of special education of vision impaired people? Are there any regional disparities? The authors applied several scientific methods – a standardized form for recording of particular contact the teacher with vision impaired person in Special Education Centre, database design, spatial analysis and map compiling. The study confirms a significant increase of disability in higher age and dominant role of the family in the care for a person with vision impaired people. The research confirmed the dominant role of regions as special needs centres authorities. Based on a unique survey the study quantified special needs centres activity.